Children’s Language Acquisition is Reviewed from The Mother Language - Eksawati, Lutfi; Dinata, Sigit Andi Prasetya; Solahudin, Agung (Universitas Sebelas Maret, 2023)
This research describes children’s language acquisition (L2), especially Indonesian, which is influenced by their mother tongue (B1), namely the regional language. This research is included in qualitative research using a qualitative descriptive approach. The data obtained in this research is linguistic data regarding language acquisition. The focus of this research is children’s language acquisition, especially Indonesian, which is influenced by their mother tongue and regional languages. Samples were collected from two geographically different areas. Namely the people of Jepara city and the people of Solo city. This research uses documentation techniques for data collection. The documents analyzed in this research are the languages that are dominant in Jepara and Solo society and are related to the acquisition of Indonesian. The validity of the data used is determined by theoretical triangulation. Data analysis in this research consists of several elements, namely data reduction or data selection (data selection and sorting), data presentation, and drawing conclusions. The results of this research are that children’s language acquisition (L2) is largely error-free and error-free. This is because children are still influenced by their mother tongue (B1). The mother tongue influences the correct and appropriate pronunciation of Indonesian (B2). This error usually occurs in Indonesian words that are similar to mother tongue vocabulary (B1).